تحسين مهارة الاستماع بتوظيف عناصر الوسائط المتعددة للطلبة الناطقين بغير العربية - Khadijah binti Hassan (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study examines the perceptions and opinions of the Arabic language learners in improving the listening skill by employing the various multimedia elements. In addition, the research also looked into the statistical differences between the method of improving listening skill using the multimedia elements “audio only”, “audio with video” and “audio with video and caption”. The data were collected through a distributed questionnaire and a quasi experiment involving a listening test of 75 students from Arabic Language and Literature department and Islamic Revealed Knowledge and Heritage Studies department, International Islamic University Malaysia. The study found that method of improving listening skill using multimedia elements is important especially when using the “audio with video” and “audio with video and caption” rather than “sound only”. A group that used a single channel performed better than the group that used the dual channel. There were no significant differences between the method of optimization “audio with video” and “audio with video and caption”. The study confirmed that the most effective approach to teach listening skill is by using “audio with video and caption” followed by “audio with video” and lastly “audio only”.